Antimicrobial Activity and Phytochemical screening of Some Traditionally Used Nepalese Medicinal Plants - Rajendra Gyawali, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Antimicrobial Activity and Phytochemical screening of Some Traditionally Used Nepalese Medicinal Plants